Bi-maxillary Protrusion: An Orthodontic Management - Chaudhary, N. K.; Giri, J.; Gyawali, R.; Pokharel, P. R. (Kathmandu University Medical Journal, 2022)
Bi-maxillary protrusion is a condition with protrusive and proclined upper and lower incisors and the patient is not able to close lips without strain. The presented case reported with the chief complaint of forwardly placed teeth, with skeletal class II malocclusion, and Angle’s class I malocclusion with protrusive and forwardly placed upper and lower incisors. The treatment was performed with the extraction of all first premolars and retraction under absolute anchorage. The retraction of upper and lower lips of about 3 mm and 3.5 mm was achieved respectively and the patient was able to close lips without strain. With proper anchorage preparation, bi-maxillary protrusion can be successfully managed orthodontically.